Atrial anti-tachycardia pacing resulting in termination of atrial flutter: intracardiac electrograms providing insight into the mechanism of arrhythmia termination. Issue 7 (July 2019) - Maeda, Shingo; Goya, Masahiko; Yagishita, Atsuhiko; Takahashi, Yoshihide; Kawabata, Mihoko; Casado Arroyo, Ruben; Hirao, Kenzo
The "MINimizE Right Ventricular pacing to prevent Atrial fibrillation and heart failure" (MINERVA) multicenter randomized study demonstrated that atrial anti-tachycardia pacing (A-ATP) can effectively decrease the burden of atrial fibrillation (AF) in patients with bradycardia and atrial tachyarrhythmias. We herein describe the unique electrophysiological results of AF ablation in a patient for whom atrial flutter (AFL) was terminated by A-ATP from a Medtronic dual-chamber pacemaker. In this case, the atrial activation sequence indicated that the tachycardia was a right atrial typical flutter and that A-ATP from the right atrial appendage would thus be more likely to terminate the tachycardia. This is a novel case involving documented intracardiac electrograms captured during an AF ablation study in a patient in whom AFL was successfully terminated by A-ATP. These findings provide insight into the mechanisms by which A-ATP can terminate atrial arrhythmias.